"Murder Me…Become a Man": Establishing the Masculine Care Circle in Young Adult Dystopia. Issue 4 (18th May 2016) - Seymour, Jessica
Abstract : Young adult (YA) dystopia, a genre which is led almost exclusively by young female protagonists, has gained much scholarly attention in recent years. While most of the academic discussions focus, rightly, on portrayals of female characters and gender performance, portrayals of masculinity have failed to elicit the same scholarly response. This article argues that YA dystopia has begun to model a more inclusive, broader approach to masculine behavior by portraying male characters in nurturing positions and forming care relationships with other characters in the narrative. These relationships form a "care circle" of dependent characters, which guides how male characters approach the performance of masculinity.